The McGill Pain Questionnaire, Japanese Version, Reconsidered: Confirming the Theoretical Structure - Mamoru Hasegawa; Suguru Hattori; Masaru Mishima; Isao Matsumoto; Takashi Kimura; Yasuko Baba; Osami Takano; Toshio Sasaki; Kazue Kanemura; Katsuhiko Senami; Toshinari Shibata (Pain Research and Management)
BACKGROUND: Based on a tripartite theoretical model of pain, the Pain Rating Index (PRI) of the McGill Pain Questionnaire (MPQ) continues to be one of the most frequently used instruments to measure clinical pain. However, language and cultural barriers have hindered its wide use and standardization in Japan. Although a number of exploratory factor analysis studies have failed to support consistently the theoretical structure of the MPQ, a few previous confirmatory factor analysis studies did statistically support the a priori model.